Mulheres em posição de liderança: obstáculos e expectativas de gênero em cargos de nível tático em Manaus - Valente, Giulia Vitória Henrique (Brasil, 2024)
This paper addresses gender inequality in tactical-level leadership positions in private companies. Focusing on the national context, it is possible to highlight the permanence of historical barriers, such as the "Glass Ceiling", which ends up making it difficult for women to advance in the labor market. Previous studies point to barriers such as gender stereotypes and questioning authority, leading them to dissatisfaction or giving up. The absence of women in leadership positions at the tactical level directly influences the under-representation at strategic levels formed by directors and presidents. Some women adopt "management masculinization" strategies to reinforce authority while others adopt a more resilient and flexible profile. The qualitative research, using a questionnaire with open questions, seeks to identify underlying causes for the lack of female representation, analyze direct and indirect barriers, and explore predominant leadership styles. This study will contribute to the dialogue on gender equality in the corporate environment and will expose the obstacles faced by the leader throughout her career. The main results were the imbalance between professional and personal life, the conflict of double shifts and the lack of financial recognition.